2016
DOI: 10.1590/1414-431x20155039
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection against experimental myocardial ischemic injury using cornin

Abstract: Phosphorylated-cyclic adenosine monophosphate response element-binding protein (Phospho-CREB) has an important role in the pathogenesis of myocardial ischemia. We isolated the iridoid glycoside cornin from the fruit of Verbena officinalis L, investigated its effects against myocardial ischemia and reperfusion (I/R) injury in vivo, and elucidated its potential mechanism in vitro. Effects of cornin on cell viability, as well as expression of phospho-CREB and phospho-Akt in hypoxic H9c2 cells in vitro, and myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…and xylazine (10 mg/kg, i.m.) 13 , needle electrodes were inserted into paw pads, and connected to Cardiart 1081 (BPL) ECG machine. ECG recordings were made using 20 mm/mV sensitivity with a paper speed of 50 mm/s in lead II position and ST-segment elevation (expressed in mV) in normal and experimental animals were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and xylazine (10 mg/kg, i.m.) 13 , needle electrodes were inserted into paw pads, and connected to Cardiart 1081 (BPL) ECG machine. ECG recordings were made using 20 mm/mV sensitivity with a paper speed of 50 mm/s in lead II position and ST-segment elevation (expressed in mV) in normal and experimental animals were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies also reported that active components of its leaves exhibit cardio protection 11 , 12 . As in some reports, iridoid glycosides such as Cornin, Picroside II and Catalpol were also shown to be effective in cardio protection 13 15 , in this investigation we thought of isolating an iridoid glycoside from the methanolic extract of its leaves and then to investigate its preventing effects on myocardial injury, if any. On the basis of its spectroscopic analyses, as described earlier in previous report 16 , the isolated compound was identified as agnucastoside-C (7-O-trans-p-coumaroyl-6-O-trans-caffeoyl-8-epiloganic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Cornin, also known as verbenalin, an iridoid monoglucoside, derived from Cornus officinalis (Choi et al, 2011), or Verbena officinalis (Xu et al, 2016), has been reported to induce apoptosis, inhibit the migration and invasion (Liao et al, 2015) and attenuate BPH (Hwangbo et al, 2018). Nevertheless, the antitumor mechanism of cornin has not been clearly determined in PCs to date.…”
Section: Introductionmentioning
confidence: 99%
“…Cornin is an iridoid glycoside derived from the fruit of Verbena officinalis L. Previous studies confirmed that cornin has inhibition effects in lipid peroxidation [15], cardioprotection against myocardial ischemic injury [16], and brain protection against cerebral ischemic injury [17,18]. However, the underlying molecular mechanism of brain protective effect during cerebral ischemia and reperfusion is unclear.…”
Section: Introductionmentioning
confidence: 99%